Towards myo-inositol based hydrogelators - Orava, Sarita (2024)
In this master’s thesis, the literature part focuses on the structural aspects, properties, and importance of myo-inositol in numerous biological functions. In addition, the potential and challenges of functionalizing myo-inositol and its ability to act as a gelator in low molecular weight gels are discussed. The aim of the experimental part was to prepare myo-inositol based amphiphilic low molecular weight gelators and investigate their gelling properties in biocompatible gels. The myo-inositol based derivatives designed in this work were 2-O-benzyl-myo-inositol and 2-O-Fmoc-myo inositol. The functionalizations were carried out according to a three-step retrosynthesis plan: regio- and stereoselective protection of myo-inositol, regioselective functionalization with the selected target molecule, and removal of the protecting groups. Benzylated myo-inositol derivative was successfully synthesized, and the reaction conditions of this reaction were optimized. Functionalization with Fmoc-moiety was performed under two different reaction conditions, but the desired Fmoc derivative could not be synthesized. In gelation experiments for benzylated myo-inositol, flake formation and partial gel were observed by increasing the concentration. Based on this result, some amphiphilic myo-inositol derivatives may have the potential to act as a gelator in biocompatible gels, but further studies are required to confirm this hypothesis.